Lipidome signatures in early bovine embryo development - Sudano, Mateus J.; Rascado, Tatiana D. S. [UNESP]; Tata, Alessandra; Belaz, Katia R. A.; Santos, Vanessa G.; Valente, Roniele S.; Mesquita, Fernando S.; Ferreira, Christina R.; Araujo, Joao P. [UNESP]; Eberlin, Marcos N.; Landim-Alvarenga, Fernanda D. C. [UNESP] (Elsevier B.V., 2016)
Mammalian preimplantation embryonic development is a complex, conserved, and well orchestrated process involving dynamic molecular and structural changes. Understanding membrane lipid profile fluctuation during this crucial period is fundamental to address mechanisms governing embryogenesis. Therefore, the aim of the present work was to perform a comprehensive assessment of stage-specific lipid profiles during early bovine embryonic development and associate with the mRNA abundance of lipid metabolism related genes (ACSL3, ELOVL5, and ELOVL6) and with the amount of cytoplasmic lipid droplets. Immature oocytes were recovered from slaughterhouse-derived ovaries, two-cell embryos, and eight- to 16-cell embryos, morula, and blastocysts that were in vitro produced under different environmental conditions. Lipid droplets content and mRNA transcript levels for ACSL3, ELOVL5, and ELOVL6, monitored by lipid staining and quantitative polymerase chain reaction, respectively, increased at morula followed by a decrease at blastocyst stage. Relative mRNA abundance changes of ACSL3 were closely related to cytoplasmic lipid droplet accumulation. Characteristic dynamic changes of phospholipid profiles were observed during early embryo development and related to unsaturation level, acyl chain length, and class composition. ELOVL5 and ELOVL6 mRNA levels were suggestive of over expression of membrane phospholipids containing elongated fatty acids with 16, 18, and 20 carbons. In addition, putative biomarkers of key events of embryogenesis, embryo lipid accumulation, and elongation were identified. This study provides a comprehensive description of stage-specific lipidome signatures and proposes a mechanism to explain its potential relationship with the fluctuation of both cytoplasmic lipid droplets content and mRNA levels of lipid metabolism-related genes during early bovine embryo development (c) 2016 Elsevier Inc. All rights reserved.
Keywords: Embryogenesis; Membrane phospholipids; Cytoplasmic lipid droplets; Long chain acyI-CoA synthetizes; Elongation of very long fatty acids